Management Audit As An Instrument In The Management Decision - Rivera León, Félix Armando (2018)
The existence of the need for information by senior managers in public or private entities for decision making, which often suffer from independent objective tests that could increase their efficiency. The auditors today direct their auditing practices towards the financial and / or operational statements perform it with a smaller scope that does not allow them to include them in their opinion or dictum. The objective of the management audit, as set out in this article, is an audit with evaluation in the management, decision making of senior management, in compliance with standards and procedures, with a sufficient scope to allow conclude or comment on these issues.